Comprehensive overview of the role of PBX1 in mammalian kidneys - Zou, Fei; Liu, Mingsheng; Sui, Yutong; Liu, Jinyu (Frontiers in Molecular Biosciences, 2023)
Pre-B-cell leukemia homeobox transcription factor 1 (PBX1) is a member of the TALE (three amino acid loop extension) family and contains an excessively conserved atypical homeodomain transcription factor (TF). When dimerized with other TALE proteins, it can act as a pioneer factor and provide regulatory sequences via interaction with partners. In vertebrates, PBX1 is expressed during the blastula stage, and its germline variations in humans are interrelated with syndromic anomalies of the kidney, which plays an important role in hematopoiesis and immunity among vertebrates. Herein, we summarize the existing data on PBX1 functions, the impact of PBX1 on renal tumors, PBX1-deficient animal models, and blood vessels in mammalian kidneys. The data indicated that the interaction of PBX1 with different partners such as the HOX gene are responsible for abnormal proliferation and variation of the embryonic mesenchyme, while truncating variants were shown to cause milder phenotypes (mostly cryptorchidism and deafness). Although such interactions have been identified to be the cause of many defects in mammals, some phenotypic variations have yet to be understood. Thus, further research on the TALE family is required.